Endometrioma: why and when it should be intervene d before infertility treat ments - Celis López, Alfredo Alonso (2015)
Endometriosis is undoubtedly one of the most enigmatic diseases in gynecology and in the medical profession. Its pathogenesis remains unknown, and its presentation is bizarre as there are women with endometriosis who have pain and/or infertility and other women with endometriosis do not suffer of either pain or infertility; also, many aspects on its handling remain controversial, including the treatment of endometrioma. Different medical and surgical treatments have been proposed with varying results, but perhaps the surgical treatment of ovarian endometrioma is most controversial. The relationship between endometrioma and infertility has always been manifest, and the treatment of choice has been surgical, with evidence of increased fertility following surgery. With the advent of in vitro fertilization (IVF) doubts appeared about the real benefit of surgery to improve fertility in women with endometrioma, as some studies referred the negative impact of surgery on ovarian reserve as healthy ovarian tissue was removed along with the endometrioma capsule. It is important to note that endometrioma not only generates infertility; pain is often most prevalent and many of these patients are not infertile. The aim of this review is to try to establish in the light of evidence the current management of endometrioma and the impact of surgery on fertility.